Human Traffic and Fire Effects On Invasive Earthworm Abundance in the Boundary Waters Canoe Area Wilderness of Northern Minnesota - Seidel, Melissa; Rothaus, Matthew (My University, 2015)
We hypothesized that worms would be more abundant near BWCA campsites and less abundant in areas burned by the Pagami Creek Fire of 2011.
Color poster with text, photographs, maps, images, graphs, and charts.
Keywords: Pagami Creek Fire; Ecosystems; Invasive species; Earthworms; Boundary Waters Canoe Area; Posters